Management and Outcome of Depressed Skull Fracture in Head Injury - Rolekar, Nikita G (Medicine and Medical Research: New Perspectives Vol. 9, 2024)
Background: Skull fracture results from large energy forces applied to the head. The extent and type of skull fracture are determined by the kinetic energy of the striking object, the geometry of the striking object, the direction of the impact force, and the anatomic site of the impact. Many changes and improvements have taken place in the management of patients with head injuries in the past 20 years. In 1980, the introduction of the Advanced Trauma Life Support (ATLS) training program helped in a better understanding of the management of trauma patients. By preventing injury, limiting trauma, and treating early, we can achieve good outcomes in patients with head injuries. Aim: The aim of this study is to find out the severity of the head injury and associated intracranial injury with depressed skull fracture (DSF) and it helps in establishing a plan of management of DSF. Materials and Methods: This is the prospective study of 50 patients with DFS visiting the Department of Surgery at Sir Sayajirao General Hospital and Medical College, Baroda, from January 2010 to March 2012. The patients selected for this study belonged to all age groups and had clinically palpable DSF. The CT scan showed DFS along with other intracranial findings such as Extradural hematoma. The principles of management were conservative as well as operative, depending on the type of fractures and intracranial findings. Results: Out of 50 patients, 32% were aged between 21 and 30 years; 94% were men and 6% were women. 30 (60%) patients had Vehicular accidents whereas 8 (16%) patients had assaults. Extradural hematoma was reported in two (11.11%) patients. 42 cases had mild head injury, 29 were managed conservatively and 13 were operated. Six cases had severe head injury; three were operated on; and three were treated conservatively. Elevation of bone fragments occasionally improves a focal neurological deficit originating in the cortex directly under a depressed bone fracture. Brain dysfunction generally undergoes a neurological recovery over a period of several weeks to months, similar to that after a stroke or a head injury without a depressed fracture. Conclusion: Early definitive diagnosis and management of depressed skull fracture reduces morbidity, and mortality and helps in achieving maximum function. The use of GCS in conjunction with the CT findings is most helpful in the early management of DSF.